THE MEDIATING ROLE OF JOB SATISFACTION ON COMPENSATION, WORK ENVIRONMENT, AND EMPLOYEE PERFORMANCE - TJAHYANTI, SETIA; PUSPITASARI, AULIA YANDA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
Job satisfaction has an important role in improving employee performance. This provides high enthusiasm and motivation for employees to improve performance. On the other hand, to improve employee performance, organizations provide compensation based on predetermined standards and the work environment. The purpose of this research was to determine the mediating role of job satisfaction on compensation, work environment, and employee performance at PT. SMJ. This form of research uses causality research. The population used in this research were all employees of PT. SMJ with 83 people. The technique used in this research was a purposive sampling technique involving 83 employees of PT. SMJ as respondent. This research data was collected using a questionnaire with likert scale measurements and analysis of variance based structural equation modelling data with partial least squares (PLS-SEM). The results of testing the hypothesis in this study show that there is a direct effect on compensation, work environment on job satisfaction and employee performance. Then job satisfaction has a direct effect on employee performance. It also shows that job satisfaction has an indirect influence on compensation and work environment on employee performance. It is hoped that future research will conduct research with a larger number of respondents and on different objects to provide better results.